Ethical Leadership and Character Education: Addressing the Digital Dilemmas of Society 5.0 - M Mahbubi (Journal of Education and Learning Sciences, 2024)
This study examines the integration of ethical leadership and character education in addressing the digital challenges of Society 5.0. It explores how educational institutions can equip students with ethical frameworks to navigate both physical and digital environments. Using a qualitative case study approach, the research investigates current educational practices, highlighting gaps in digital ethics integration within curricula and inconsistencies in teacher training. The findings reveal a pressing need for a structured, comprehensive framework that embeds ethical leadership into digital education, enabling students to apply ethical principles in real-world digital interactions. Furthermore, the study identifies key barriers, such as the lack of standardized digital ethics guidelines and limited institutional support for teachers. To address these challenges, the research proposes several recommendations: enhancing digital ethics education through structured curricula, improving teacher preparation programs to include digital ethics training, and fostering collaboration between educators, policymakers, and technology experts. By combining traditional character education with digital ethics, educational institutions can bette prepare students for the ethical complexities of Society 5.0. These measures are crucial for developing responsible digital citizens who can critically assess ethical dilemmas and contribute positively to a rapidly evolving technological landscape.